Contribution of the mutation rs8193069 in TLR4 to mastitis resistance and performance in Holstein cows in southern China. Issue 1 (22nd November 2021) - Chen, Hongbo; Liu, Chenhui; Xiang, Min; Yu, Jie; Xia, Yu; Hu, Xiuzhong; Wang, Dingfa; Tao, Bifei; Zhang, Yongjin; Cheng, Lei
Abstract: Bovine mastitis has become increasingly important issues for farmers and consumers, leading to large economic losses in the dairy industry worldwide. Because treatment of mastitis is difficult and costly, improved mastitis resistance through selective breeding would be advantageous. The toll‐like receptor 4 ( TLR4 ) is an important player in recognising pathogens and activating immune responses. However, its roles in mastitis occurrence and the underlying molecular mechanisms are unclear. In this study, a single nucleotide polymorphism, rs8193069 (T → C) in TLR4 gene was detected in a Holstein cow resource population in southern China. Association analysis with 5‐year production traits, haematology, and biochemistry parameters revealed that individuals with genotype CC had significantly lower somatic cell counts (SCC), lower fat percentage, but higher 305‐day milk ( p  < 0.05) and total milk yield ( p  < 0.01). Both genotypes CC and CT had lower lymphocyte counts (#LYMPH) ( p  < 0.01) and basophil counts (#BASO) ( p  < 0.05) than TT. Genotype CC had a less level of triglyceride ( p  < 0.01) and creatine kinase ( p  < 0.05) than CT. Further analysis based on the production data revealed significant positive correlations between SCC and #LYMPH. Analysis of TLR4 protein structure and properties suggested that the missense mutation on the 674th amino acid from Thr to Ile reduced the flexibility and hydrophilicity of TIR domain, implying a weakened binding ability of TLR4 to its adaptors. In conclusion, allele C of rs8193069 was the major allele in Holstein cows that indicated a greater genetic potential to mastitis resistance and milk yields, probably via the LPS‐TLR4 inflammatory signalling. This study offers a marker to improve mastitis resistance in the dairy cow population in southern China. Abstract : A single nucleotide polymorphism, rs8193069 (T → C) in TLR4 gene was detected in 785 Holstein cows from southern China. The rs8193069 of TLR4 is significantly associated with both performance traits and blood parameters in Holstein cows. The mutation of rs8193069 from T to C contributes the mastitis resistance with decreased SCC in milk, probably by weakening the binding ability of the TIR domain to TLR4 adaptors and LPS/TLR4‐NF‐κB signalling mediated inflammation.